Risks and security of information: convergences from records management - García-Morales, Elisa (Anuario ThinkEPI, 2016)
A rapprochement between disciplines that addresses information security management, risk management, and records management is necessary for organizations to adopt the best strategy in a complex scenario of digital transformation. There are many points of convergence between disciplines, and our experience in the banking sector has shown that a program of information governance is necessary to facilitate collaboration between different professionals.